Pengaruh Penerapan Model Pembelajaran Terhadap Sikap Religius Siswa pada Mata Pelajaran Pendidikan Pancasila dan Kewarganegaraan - Ramdani, Emi; Marzuki, Marzuki (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2019)
This article aims to describe the effect of applying learning models (discovery learning, problem-based learning, and project-based learning) for   students’ religious attitudes. The study used a quantitative approach, that a sample of 120 junior high school students in the Bantan District. Data collection using a questionnaire with 72 questions. Data analysis uses multiple linear regression. The results of the study indicate that the application of the discovery learning model and project-based learning have very high frequencies. The problem-based learning model has a high frequency. The learning model which has the greatest influence on the religious character of students is discovery learning with a sig value of 0.000<0.05 and a calculated t value of 5.38>1.98. The second sequence is project-based learning with a sig value of 0.001 <0.05 and t value of 3.32>1.98. The problem-based learning is in third place with a sig value of 0.01 <0.05 and t value of 2.63>1.98.